Zinc accumulation aggravates cerebral ischemia/reperfusion injury by promoting inflammation - Li, Wei; Yang, Xueqi; Ding, Mao; Shi, Wenjuan; Huang, Yuyou; An, Qi; Qi, Zhifeng; Zhao, Yongmei (Frontiers in Cellular Neuroscience, 2023)
Intracellular zinc accumulation has been shown to be associated with neuronal death after cerebral ischemia. However, the mechanism of zinc accumulation leading to neuronal death in ischemia/reperfusion (I/R) is still unclear. Intracellular zinc signals are required for the production of proinflammatory cytokines. The present study investigated whether intracellular accumulated zinc aggravates I/R injury through inflammatory response, and inflammation-mediated neuronal apoptosis. Male Sprague–Dawley rats were treated with vehicle or zinc chelator TPEN 15 mg/kg before a 90-minute middle cerebral artery occlusion (MCAO). The expressions of proinflammatory cytokines TNF-α, IL-6, NF-κB p65, and NF-κB inhibitory protein IκB-α, as well as anti-inflammatory cytokines IL-10 were assessed at 6 or 24 h after reperfusion. Our results demonstrated that the expression of TNF-α, IL-6 and NF-κB p65 increased after reperfusion, while the expression of IκB-α and IL-10 decreased, suggesting that cerebral ischemia triggers inflammatory response. Furthermore, TNF-α, NF-κB p65 and IL-10 were all colocalized with the neuron-specific nuclear protein (NeuN), suggesting that the ischemia-induced inflammatory response occurs in neurons. Moreover, TNF-α was also colocalized with the zinc-specific dyes NG, suggesting that intracellular accumulated zinc might be associated with neuronal inflammation following cerebral I/R. Chelating zinc with TPEN reversed the expression of TNF-α, NF-κB p65, IκB-α, IL-6 and IL-10 in ischemic rats. Besides, IL-6-positive cells were colocalized with TUNEL-positive cells in the ischemic penumbra of MCAO rats at 24 h after reperfusion, indicating that zinc accumulation following I/R might induce inflammation and inflammation-associated neuronal apoptosis. Taken together, this study demonstrates that excessive zinc activates inflammation and that the brain injury caused by zinc accumulation is at least partially due to specific neuronal apoptosis induced by inflammation, which may provide an important mechanism of cerebral I/R injury.